Business etiquette in 12 countries: special considerations for female expatriates. (2nd December 2009) - Gruys, Melissa L.; Stewart, Susan M.; Patel, Trupti
The current paper provides a summary and highlights issues that are specific to female expatriates completing assignments in 12 different countries from four regions around the world. The regions and countries reviewed include North America (USA, Mexico, Canada), Europe (Spain, France, Italy), Middle East (Saudi Arabia, Israel, Afghanistan) and Asia (Korea, China, Japan). The information provided will be of assistance to female expatriates who are making preparations to travel to any of the countries reviewed and might also help decision-makers focus on how women can be effectively utilised in global business assignments and transactions.